Analisis Tindak Tutur Direktif Novel Bumi Cinta Karya Habiburrahman El Shirazy - Zulaikha, Rifa Dewi; Rahmawati, Endang (ESTETIK : Jurnal Bahasa Indonesia, 2021)
This study discusses the directive acts of the novel Bumi Cinta by Habiburrahman El Shirazy and the directive acts of the directive acts of the novel Cinta Cinta by Habiburrahman El Shirazy. This type of research is a qualitative descriptive study. The theory used is the theory of Harun Joko Prayitno. The data source of this research is a speech in the novel Bumi Cinta by Habiburrahman El Shirazy. The research data consisted of utterances cited by directive speech acts which included directive speech acts and directive speech acts in the novel Bumi Cinta by Habiburrahman El Shirazy. Data were obtained by referring to the competent free engage listening technique obtained by note taking. The validity of the data in this study uses theory triangulation. Research results in the novel Bumi Cinta found six forms of directive speech acts, on request, request, invitation, approval, criticism and prohibition. When viewed, the directive speech function of the novel Bumi Cinta has a variety of functions. The form of directive speech acts requires the functions of ordering, commanding, asking, activating and letting. The form of directive speech acts requests, requests, hopes and offers. The form of speech act directive invitation has the function of inviting, persuading, supporting and asking. The form of directive speech acts to support the functions of advising, asking, asking and reminding. The form of directive speech acts of criticism has the function of reprimanding and winning. The form of directive speech acts have a ban function.